Transcriptional signatures of Mycobacterium tuberculosis in mouse model of intraocular tuberculosis. Issue 5 (5th September 2019) - Abhishek, Sudhanshu; Ryndak, Michelle Beth; Choudhary, Alpa; Sharma, Sumedha; Gupta, Amod; Gupta, Vishali; Singh, Nirbhai; Laal, Suman; Verma, Indu
ABSTRACT: Background: Studies on human intraocular tuberculosis (IOTB) are extremely challenging. For understanding the pathogenesis of IOTB, it is important to investigate the mycobacterial transcriptional changes in ocular environment. Methods: Mice were challenged intravenously with Mycobacterium tuberculosis H37Rv and at 45 days post-infection, experimental IOTB was confirmed based on bacteriological and molecular assays. M. tuberculosis transcriptome was analyzed in the infected eyes using microarray technology. The identified M. tuberculosis signature genes were further validated and investigated in human IOTB samples using real-time polymerase chain reaction. Results: Following intravenous challenge with M. tuberculosis, 45% (5/12) mice showed bacilli in the eyes with positivity for M. tuberculosis ribonucleic acid in 100% (12/12), thus confirming the paucibacillary nature of IOTB similar to human IOTB. M. tuberculosis transcriptome in these infected eyes showed significant upregulation of 12 M. tuberculosis genes and five of these transcripts ( Rv0962c, Rv0984, Rv2612c, Rv0974c and Rv0971c ) were also identified in human clinically confirmed cases of IOTB. Conclusions: Differentially expressed mycobacterial genes identified in an intravenously challenged paucibacillary mouse IOTB model and presence of these transcripts in human IOTB samples highlight the possible role of these genes for survival of M. tuberculosis in the ocular environment, thus contributing to pathogenesis of IOTB. Abstract : M. tuberculosis transcriptional signatures identified in the eyes of infected animals and validated in human intraocular tuberculosis (IOTB) vitreous samples explain the molecular pathogenesis of IOTB and may aid in development of diagnostics for IOTB.